Case Report: Peptic Ulcer and Anemia Gravis Due to Over-the-Counter Anti-Inflammatory Drugs Misuse in Gout Arthritis - Mubaraq, Syahrun El; Nawangasri, Andis Putri; Syabany, Muhammad Noer; Suling, Irmawati (Universitas Muhammadiyah Surakarta, 2024)
Background: Peptic ulcer disease (PUD) is a serious global health concern, often linked to nonsteroidal anti-inflammatory drugs (NSAIDs). Chronic, unsupervised NSAID use increases the risk of severe gastrointestinal complications, particularly in rural areas with limited healthcare access. Case Presentation: A 62-year-old male from a remote village presented with hematemesis, melena, and severe anemia (Hb 6.7 g/dL). He had a history of prolonged NSAID and steroid use for gout arthritis without medical supervision. Due to limited diagnostic facilities, the diagnosis of NSAID-induced peptic ulcer with anemia was based on clinical and laboratory findings. The patient received blood transfusions, proton pump inhibitors, gastroprotective agents, and urate-lowering therapy. His condition improved after seven days of hospitalization, and he was discharged with medication guidelines and follow-up care. Discussion: This case highlights the dangers of self-medication and the lack of awareness regarding NSAID-associated complications in underserved regions. Alternative pain management strategies, including colchicine and lifestyle modifications, should be prioritized to reduce reliance on NSAIDs. Conclusion: Chronic NSAID misuse can lead to life-threatening complications, as demonstrated in this case of peptic ulcer and anemia gravis. This report emphasizes the need for better patient education, medication supervision, and stricter regulations on over-the-counter drug sales, especially in rural settings.